Odpowiedź:
x + 5 i 1/7 = 10
x = 10 - 5 i 1/7 = 9 i 7/7 - 5 i 1/7
x = 4 i 6/7
spr 4 i 6/7 + 5 i 1/7 = 9 i 7/7 = 10
2 i 1/3 + x = 6
x = 6 - 2 i 1/3 = 5 i 3/3 - 2 i 1/3
x = 3 i 2/3
spr 2 i 1/3 + 3 i 2/3 = 5 i 3/3 = 6
7 i 4/9 - x = 2 i 1/9
x = 7 i 4/9 - 2 i 1/9
x = 5 i 3/9
spr 7 i 4/9 - 5 i 3/9 = 2 i 1/9
x - 2 i 3/4 = 5 i 3/4
x = 5 i 3/4 + 2 i 3/4
x = 7 i 6/4
spr 7 i 6/4 - 2 i 3/4 = 5 i 3/4
8 i 9/10 + x = 12 i 7/10
x = 12 i 7/10 - 8 i 9/10 = 11 i 17/10 - 8 i 9/10
x = 3 i 8/10
spr 8 i 9/10 + 3 i 8/10 = 11 i 17/10 = 12 i 7/10